DAMPAK FUNGSIONAL RUMAH ADAT SUKU ANUNUT TERHADAP PERKEMBANGAN IMAN ANGGOTA SUKU DI LINGKUNGAN BENTENG GADING PAROKI STA. MARIA MEDIATRIX OMNIUM GRATIARUM KEUSKUPAN ATAMBUA - Anunut, Yohanes; Tukan, Antonius I.N.; Hayon, Vinsensius (Pastoralia Jurnal Penelitian Dosen, 2020)
One of the cultural elements in society, especially members of the Anunut tribe, respects the traditional house as a legacy from their ancestors which is sometimes seen as a cultural perspective. The form of traditional houses is not the same in every tribe. But basically have the same function. In the theoretical basis, the author uses the biblical foundation of the Old Testament, New Testament, theological, pastoral and cultural. The hypothesis developed in this paper is the function of the Anunut tribal house as a unifying tool as well as a symbol of the presence of the highest form. Based on the analysis of the interview data, it is known that the understanding of the members of the tribe is still lacking due to the very low education of the community so that the members of the tribe only understand it to the extent of custom which causes the dualism of faith. The inhibiting factor is the lack of involvement of Anunut tribe members in spiritual activities at the church and ceremonial materials. The supporting factor is involving all members of the Anunut tribe in tribal ceremonies, providing motivation and appreciating the implementation of adat. Efforts made, namely the Benteng Gading neighborhood committee, involve members of the Anunut tribe in spiritual activities in the church and in the environment so that the tribal members' faith system radiates the brotherly love of Jesus Christ in the life of faith.